Social Media Utilization Among Shoulder and Elbow Surgeons. Issue 3 (1st February 2021) - Narain, Ankur S.; Dhayalan, Arjun; Weinberg, Maxwell; Latario, Luke D.; Shuman, Matthew E.; Bango, Jugert; Holmes, Sara; Patel, Jay K.; Chan, Wayne; Aaron, Daniel L.
Abstract : Introduction: Social media represents a novel platform for patient-physician interaction. Although social media utilization patterns have been analyzed in other fields, no such study has been performed in shoulder and elbow specialists. Methods: The membership database of the society of the American Shoulder and Elbow Surgeons was queried. Online searches were performed to identify if each surgeon had professional profiles on popular social media platforms. A social media score was then calculated, defined as the number of active accounts. Statistical analysis was used to test for associations between demographics and social media utilization. Results: Six hundred seventy-six surgeons were analyzed. The average social media score was 1.61. The most highly used platform was LinkedIn (61%). The least used platform was Instagram (5% active, 11% total). Female surgeons were more likely to use Instagram than men (12.5% versus 4.9%). Academic surgeons were more likely to use ResearchGate (46.5% versus 33.3%), whereas private practice surgeons were more likely to have a website (19.9% versus 11.7%). Practitioners from the South had the lowest social media utilization. Conclusions: Shoulder and elbow surgeons underuse social media. As the influence of social media continues to grow, it will be important for surgeons to implement social media within their practices.